2015
DOI: 10.1007/s10344-015-0917-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal distribution of rabies in Arctic foxes in Greenland

Abstract: The temporal occurrence, spatial distribution, spread, and prevalence of rabies in Arctic foxes, Vulpes lagopus, in Greenland were studied using historical observations from 1969 to 2011 and survey data collected in the winters 1992 and 1993. Regionally, the prevalence of rabies ranged between 0 and 7.1 %. Wavelet analysis was used to identify periodicities in the abundance of rabies cases based on the historical observations. No general length of the cyclic interval of rabies occurrences in Greenland could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Interestingly, the most ancestral RABV still circulating (subclade arctic 3.II) has the widest geographic spread across the entire western part of Greenland. Such spread has also been demonstrated epidemiologically [ 13 ]. The dynamic observed here is further demonstrated by the observation that older subclades previously found in Greenland ( Fig 2 ), [ 15 18 ] seem to have disappeared.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Interestingly, the most ancestral RABV still circulating (subclade arctic 3.II) has the widest geographic spread across the entire western part of Greenland. Such spread has also been demonstrated epidemiologically [ 13 ]. The dynamic observed here is further demonstrated by the observation that older subclades previously found in Greenland ( Fig 2 ), [ 15 18 ] seem to have disappeared.…”
Section: Discussionmentioning
confidence: 89%
“…These results may be useful for future control strategies of arctic fox rabies. In contrast to previous statements [ 13 ], given the unique geographical location of Greenland, the expected reduction of connectivity by pack-ice due to climate change [ 54 , 55 ] and the geographic separation of individual host and virus genetic subclades despite long distance movement [ 36 ], the idea of arctic rabies control using oral rabies vaccination (ORV) in selected coastal areas appears feasible [ 56 , 57 ]. While preliminary field trials in Newfoundland (Canada) [ 58 ] and even northern Greenland [ 59 ] demonstrated in principle that ORV could be undertaken in remote northern regions, a targeted vaccination strategy would have to be developed before an elimination program could be implemented.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations